Evaluation of statewide utilization of helicopter emergency medical services for interfacility transfer. Issue 3 (September 2021) - Udekwu, Pascal; Stiles, Anquonette; Tann, Kimberly; McIntyre, Sarah; Roy, Sara; Schiro, Sharon
Abstract : BACKGROUND: Helicopter emergency medical services (HEMSs) are used with increasing frequency for the transportation of injured patients from the scene and from treatment facilities to higher levels of care. Improved outcomes have been difficult to establish, and reports of overutilization and financial harm have been published. Our study was performed to evaluate statewide utilization for interfacility transfers (IFTs). METHODS: Data from the North Carolina state trauma registry from 2013 to 2017 were evaluated and ground, and helicopter IFTs were compared. RESULTS: Overall interfacility use of HEMSs peaked at 7, 861 patient transports in 2016, and the percent of all IFTs fell from 17% to 13.3% over the study period. Helicopter emergency medical services patients were more likely to be male (69.8%) and younger (48.0 vs. 56.2 years), and have higher Injury Severity Scores (14.6 vs. 9.0) and higher mortality (10.5% vs. 2.8%) than ground emergency medical services (GEMSs) patients. When adjusted for age, sex, Injury Severity Score, and transport distance, HEMSs survival was significantly higher (odds ratio, 0.353; 95% CI, 0.308–0.404; p < 0.0001). Normal prehospital vital signs (VSs) and Glasgow Coma Scale score motor component (GCS-M) were associated with low mortality rates in both groups. Abnormal prehospital VSs and GCS-M were associated with an 11.8% mortality rate in HEMSs patients and 3.1% in GEMSs patients. Normal referring facility VSs and GCS-M did not confer similar protection with a mortality rate of 10.0% in HEMSs patients and 2.8% in GEMSs. Changes in prehospital to referring facility VSs did not demonstrate a low mortality group. Abbreviated Injury Scale and changes in VSs did not identify HEMSs transport benefit groups. CONCLUSION: The proportion of HEMSs transfers fell over the study period and, while associated with a 10.5% mortality rate, had an outcome benefit compared with GEMSs. These patients could not be sorted into risk categories for transportation choice based on VSs or GCS-M derangement or by changes thereof, and opportunities for system improvement were not identified. LEVEL OF EVIDENCE: Prognostic/epidemiological study, level III; Care Management, level IV.